Variable Effects of Non-steroidal Anti-inflammatory Drugs (NSAIDs) on Selected Biochemical Processes Mediated by Soil Microorganisms - Cycoń, Mariusz; Borymski, Sławomir; Żołnierczyk, Bartłomiej; Piotrowska-Seget, Zofia (Frontiers in Microbiology, 2016)
Non-steroidal anti-inflammatory drugs (NSAIDs) are the most frequently used group of pharmaceuticals. The high consumption and the uncontrolled disposal of unused drugs into municipal waste or their deposit in landfills can result in an increased concentration of these compounds in soils. Moreover, these drugs can affect the microbial activity. However, there is a lack of knowledge about these effects or it is very limited. Therefore, the objective of this study was to compare the impact of selected commercially available NSAIDs, i.e. diclofenac (DCF), naproxen (NPX), ibuprofen (IBF) and ketoprofen (KTP), applied at concentrations of 1 and 10 mg/kg soil, on the activity of soil microorganisms during the 90-day experiment. To ascertain this impact, substrate-induced respiration (SIR), soil enzyme activities, i.e. dehydrogenase (DHA), acid and alkaline phosphatases (PHOS-H and PHOS-OH) and urease (URE) as well as changes in the rates of nitrification and ammonification processes were determined. In addition, the number of culturable bacteria and fungi were enumerated. In general, the obtained data showed a significant stimulatory effect of NSAIDs on the microbial activity. Higher concentrations of NSAIDs caused a greater effect, which was observed for SIR, PHOS-H, PHOS-OH, URE, N-NO3- and N-NH4+, even during the whole incubation period. Moreover, the number of heterotrophic bacteria and fungi increased significantly during the experiment, which was probably a consequence of the evolution of specific microorganisms that were capable of degrading NSAIDs and used them as an additional source of carbon and energy. However, an inhibitory effect of NPX, IBF or KTP for SIR, DHA, on both phosphatases and culturable bacteria and fungi was observed at the beginning of the experiment. At lower concentrations of NSAIDs, in turn, the effects were negligible or transient. In conclusion, the application of NSAIDs altered the biochemical and microbial activity of soil what may cause the disturbance in soil functioning. It is reasonable to assume that some components of the NSAID formulations could stimulate soil microorganisms, thus resulting in an increase in biochemical activities of the soil.